The power of a brand ambassador twice influences brand image and purchase intention on Scarlett whitening beauty product - Rosari, Theodora Lady; Simamora, Bilson (Association for Scientific Computing Electrical and Engineering (ASCEE), 2024)
Many beauty products, including Scarlett Whitening products, use brand ambassadors in their promotions. One of the hype beauty products among Indonesians is Scarlett Whitening by Felicya Angelista. Regarding the influence of brand ambassadors on purchase intention, previous studies have shown inconsistent results. This research aims to determine the power of brand ambassadors in influencing brand image and purchase intention for Scarlett Whitening beauty products. This research replicates previous model by differentiating the research context. The concepts used to support this research are brand ambassador, brand image, and purchase intention. The object of this research is Scarlett Whitening's product. Data were collected using questionnaires distributed through Google Forms to 151 respondents who had ever bought and used Scarlett Whitening, selected judgmentally. Using Structural Equation Modeling (SEM) with the help of WarpPLS 8.0 as the data analysis tool, the study found that brand ambassadors' power positively influences the brand image and purchase intention. The author suggests companies consider adding product variants for other skin types. Future researchers can add or use different variables to enrich these research findings.